Pure laparoscopic right hemihepatectomy using the caudodorsal side approach (with videos). (15th June 2018) - Maeda, Koki; Honda, Goro; Kurata, Masanao; Homma, Yuki; Doi, Manami; Yamamoto, Jun; Ome, Yusuke
Abstract: Background: In our process of standardizing laparoscopic right hemihepatectomy (Lap‐RH), we found several advantages of the laparoscopic caudate lobe first approach by using a unique laparoscopic caudodorsal view. Methods: Between April 2012 and October 2017, 21 patients underwent pure Lap‐RH at our hospital. The mean patient age was 62 years (range 36–75 years), and there were more male than female patients (66.7%). Of 21 patients, 11 had hepatocellular carcinoma, eight had metastatic tumor, and the other two had focal nodular hyperplasia and refractory liver abscess. All 21 patients had Child–Pugh class A liver function. The surgical technique was recorded on video. Results: The mean operative time was 409 min (range 241–522 min), and the mean blood loss was 279 g (range 0–1, 010 g). No procedure was converted to open surgery. With regard to postoperative complications, one patient had bile leakage from the stump of the main Glissonean branch and another patient had abscess formation in the subphrenic space. No postoperative bleeding, hepatic failure, and mortality occurred. Conclusions: Our standardized procedure of Lap‐RH using the unique laparoscopic caudodorsal view is not only feasible but also confers a true advantage of the laparoscopic approach. Abstract : Highlight Maeda and colleagues describe a procedure for laparoscopic right hemihepatectomy characterized by the caudate lobe first approach, in which the caudate lobe is divided from the dorsal side utilizing a unique laparoscopic caudodorsal view. This procedure is not only feasible but also harnesses the true advantages of the laparoscopic approach.